Comparison of diagnostic performances among bronchoscopic sampling techniques in the diagnosis of peripheral pulmonary lesions - Boonsarngsuk, Viboon; Kanoksil, Wasana; Laungdamerongchai, Sarangrat (Journal of Thoracic Disease; Vol 7, No 4 (April 28, 2015): Journal of Thoracic Disease, 2015)
Background: There are many sampling techniques dedicated to radial endobronchial ultrasound (R-EBUS) guided flexible bronchoscopy (FB). However, data regarding the diagnostic performances among bronchoscopic sampling techniques is limited. This study was conducted to compare the diagnostic yields among bronchoscopic sampling techniques in the diagnosis of peripheral pulmonary lesions (PPLs). Methods: A prospective study was conducted on 112 patients who were diagnosed with PPLs and underwent R-EBUS-guided FB between Oct 2012 and Sep 2014. Sampling techniques—including transbronchial biopsy (TBB), brushing cell block, brushing smear, rinsed fluid of brushing, and bronchoalveolar lavage (BAL)—were evaluated for the diagnosis. Results: The mean diameter of the PPLs was 23.5±9.5 mm. The final diagnoses included 76 malignancies and 36 benign lesions. The overall diagnostic yield of R-EBUS-guided bronchoscopy was 80.4%; TBB gave the highest yield among the 112 specimens: 70.5%, 34.8%, 62.5%, 50.0% and 42.0% for TBB, brushing cell block, brushing smear, rinsed brushing fluid, and BAL fluid (BALF), respectively (P